8332 When cold becomes critical: educational insights from a rare case of raynaud’s phenomenon & dactylitis in infancy - Awan, Irum; Mistry, Amisha; Sridhar, Arani (Archives of disease in childhood, 2025)
BackgroundRaynaud’s phenomenon is a rare vascular disorder characterized by episodic color changes in response to cold exposure. Its occurrence in infants is extremely uncommon, with only a few documented cases. Typically, Raynaud’s in young children is associated with an underlying condition, making isolated presentations particularly significant.AimTo describe an unusual presentation of Raynaud’s phenomenon and dactylitis in an infant, emphasizing the educational value of prompt recognition and a multidisciplinary approach to improve outcomes in rare pediatric cases.MethodsThe case was documented through direct patient observation, caregiver interviews, and a review of the patient’s medical records, including imaging and laboratory results. Clinical progression, multidisciplinary consultations, and treatment outcomes were systematically recorded to provide a comprehensive overview of the presentation and management of Raynaud’s phenomenon in an infant.ResultsA female infant presented with episodic color changes and swelling of her fingers and toes over two months, triggered by cold exposure. Clinical examination revealed severe cold-induced dactylitis and Raynaud’s phenomenon extending to the proximal forearm. Comprehensive investigations, including autoimmune and inflammatory markers such as ANA, ENA, ESR, and CRP, ruled out secondary causes. The patient was managed through a multidisciplinary team (MDT) approach, involving pediatric, rheumatology, and cardiology specialists. Treatment with ibuprofen managed inflammation and pain associated with dactylitis, while omeprazole provided gastroprotection, resulting in decreased swelling. Preventive measures against cold injury, including informational leaflets, were advised. Follow-up assessments showed good overall health, with normal cardiac findings.ConclusionThis case illustrates the rare occurrence of severe infantile Raynaud’s phenomenon with dactylitis, extending beyond typical presentations. It underscores the need for heightened awareness among clinicians regarding the potential severity of Raynaud’s phenomenon in infants, necessitating a multidisciplinary approach for optimal management. Early recognition and intervention are crucial to prevent complications. Further research is needed to clarify the etiology of isolated Raynaud’s phenomenon in infants, establish standardized diagnostic criteria, and determine effective management strategies. Additionally, questions remain about the long-term outcomes and potential complications associated with early-onset Raynaud’s phenomenon, which are essential for improving care and quality of life for affected patients.ReferencesGarner R, Kumari R, Lanyon P, et al. Prevalence, risk factors and associations of primary raynaud’s phenomenon: systematic review and meta-analysis of observational studies. BMJ Open. 2015;5:e006389.Goldman RD. Raynaud phenomenon in children. Can Fam Physician. 2019;65:264.Boin F, Wigley FM. Understanding, assessing and treating raynaud’s phenomenon. Curr Opin Rheumatol. 2005;17:752.Block JA, Sequeira W. Raynaud’s phenomenon. Lancet 2001;357:2042.Wigley FM. Clinical practice. Raynaud’s phenomenon. N Engl J Med. 2002;347:1001.